The Lake Chad Development and Climate Resilience Action Plan - Lake Chad Basin Commission (World Bank, Washington, DC, 2016)
The Lake Chad Climate resilience action plan outlines the concept that there is a need to turn Lake Chad into a rural hub for regional development in parallel to the restoration of peace and security. The Plan intends to contribute significantly to food security, employment, and the social inclusion of the youth by improving, in a sustainable way, the living conditions of populations settled on the Lake’s banks and islands as well as the resilience of a system characterized by a strong demographic growth, high hydrological variability, and climate uncertainty. To achieve it, the Action Plan proposes actions in seven Priority Themes based on observations and knowledge currently available. The four riparian States plus the Central African Republic and Libya, local powers (local governments or customary authorities), Lake Chad Basin Commission (LCBC), and the civil society will be responsible for implementing the proposed actions. The Plan includes enhancing the capacity of LCBC in terms of data collection, sharing of information, and carrying out analyses useful to governance of the basin`s shared natural resources. The success of this Plan requires continuing on-going efforts to strengthen the LCBC. The tentatively estimated cost of the Lake Chad Action Plan is about 916 million Euros.